P.075 EEG features reflecting the neurodevelopmental assessment at term equivalent age in preterm born infants. (June 2022) - Dufour, A; Gagnon, M; Marandyuk, B; Mahdi, Z; Côté-Corriveau, G; Nuyt, A; Dehaes, M; Luu, T; Simard, M; Pinchefsky, EF
Abstract : Background: In Canada, 7% of children are born preterm between 29 and 36 weeks gestational age (GA). Electroencephalography (EEG) provides a bedside evaluation of brain activity, yet the clinical significance of several EEG patterns requires further study. The goal of this study is to determine the EEG features at term equivalent age (TEA) that correlate with neurodevelopmental evaluation at TEA in infants born between 29-36 weeks GA. Methods: Prospective cohort study of preterm infants born 29-36 weeks GA with 1 hour EEG recording at TEA. EEG discontinuity index (proportion <25mcV amplitude) and spectral power densities were calculated as well as the mean and maximum values of interburst intervals. At TEA, neurodevelopment was evaluated using the General Movement Optimality Score (GMOS) . Linear regression analyses were used to evaluate the association between EEG features and neurodevelopmental assessment. Results: Eighty-two children (median GA 33.6 weeks) were included (47 males). Median GMOS was 29.0 (IQR 24.3-35.0). A greater EEG discontinuity index was associated with reduced GMOS (B -6.85; 95% CI -12.13, -1.57; p=0.012). Conclusions: At TEA, a greater EEG discontinuity index was associated with a more abnormal neurodevelopmental assessment. Ongoing longitudinal neurodevelopmental assessments are needed to better evaluate the prognostic potential of TEA EEG.